Effect of Ejaculation Frequency on Semen Quality of Bali Cattle - Tamiyadi, A.; Yusuf, M.; Sahiruddin, S.; Diansyah, A.M.; Masturi, M.; Nurgina, A.T. (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2026)
Semen quality is influenced by the frequency of ejaculation, which is significant to semen characteristics. The purpose of this study was to analyze the effect of ejaculation frequency on the quality of fresh Bali cattle semen, which includes volume, motility, and concentration of spermatozoa at the AI Center Pucak Maros. This study used secondary data from production records (recording) derived from 5 Bali cattle males, with a frequency of ejaculation of 2 times. The results showed that the frequency of ejaculation was statistically significantly different (P<0.05) in semen volume in males 11442 and 11434; the percentage of motility was significantly different (P<0.05) in male 11539; and the concentration of spermatozoa was significantly different (P<0.05) in males 11442, 11434, and 11539. The correlation coefficients for the three quality parameters showed negative correlations between semen volume and motility (R=-0.531) and concentration (R=-0.414), whereas motility and concentration were positively correlated (R=0.740). In conclusion, the second ejaculation has an impact on increasing semen volume but will reduce the percentage of motility and concentration of spermatozoa. Keywords: ejaculation frequency, Balinese cattle, volume, motility, concentration